A Bile Duct‐on‐a‐Chip With Organ‐Level Functions. Issue 4 (28th October 2019) - Du, Yu; Khandekar, Gauri; Llewellyn, Jessica; Polacheck, William; Chen, Christopher S.; Wells, Rebecca G.
Abstract : Background and Aims: Chronic cholestatic liver diseases, such as primary biliary cholangitis (PBC) and primary sclerosing cholangitis (PSC), are frequently associated with damage to the barrier function of the biliary epithelium. Here, we report on a bile duct‐on‐a‐chip that phenocopies not only the tubular architecture of the bile duct in three dimensions, but also its barrier functions. Approach and Results: We showed that mouse cholangiocytes in the channel of the device became polarized and formed mature tight junctions, that the permeability of the cholangiocyte monolayer was comparable to ex vivo measurements, and that cholangiocytes in the device were mechanosensitive (as demonstrated by changes in calcium flux under applied luminal flow). Permeability decreased significantly when cells formed a compact monolayer with cell densities comparable to those observed in vivo . This device enabled independent access to the apical and basolateral surfaces of the cholangiocyte channel, allowing proof‐of‐concept toxicity studies with the biliary toxin, biliatresone, and the bile acid, glycochenodeoxycholic acid. The cholangiocyte basolateral side was more vulnerable than the apical side to treatment with either agent, suggesting a protective adaptation of the apical surface that is normally exposed to bile. Further studies revealed a protective role of the cholangiocyte apical glycocalyx, wherein disruption of the glycocalyx with neuraminidase increased the permeability of the cholangiocyte monolayer after treatment with glycochenodeoxycholic acid. Conclusions: This bile duct‐on‐a‐chip captured essential features of a simplified bile duct in structure and organ‐level functions and represents an in vitro platform to study the pathophysiology of the bile duct using cholangiocytes from a variety of sources.